Mixed Phenotype of Emphysema and Airway Wall Thickening Is Associated with Frequent Exacerbation in Chronic Obstructive Pulmonary Disease Patients - Lim, Jeong Uk (Int J Chron Obstruct Pulmon Dis, 2019)
OBJECTIVE: The presence of both emphysema and airway wall thickening determined via volumetric computed tomography (CT) is defined as mixed phenotype. The long-term clinical course of this phenotype has not been studied in depth. This study compared the mixed phenotype to other phenotypes of chronic obstructive pulmonary disease (COPD) patients. METHODS: COPD patients enrolled in the Korean Obstructive Lung Disease (KOLD) study from June 2005 to October 2015 were evaluated. The emphysema index and the percentage of bronchial mean wall area were calculated from volumetric CT scans. Patients with COPD were classified into four phenotypes using two cutoffs: emphysema index of 15% and median value of mean wall area (MWA%). RESULTS: Of 435 patients with COPD, 99 (22.8%) were defined as CT-normal type, 119 (27.4%) as emphysema-dominant type, 113 (26.0%) as airway-dominant type, and 104 (23.9%) as mixed type. The mixed phenotype showed the highest baseline total COPD Assessment Test (CAT) and St. George’s Respiratory Questionnaire (SGRQ) scores. Moreover, it had the highest proportion of patients experiencing exacerbation of COPD (50.0%), and had the lowest baseline FEV1. Lower BMI, GOLD stages III–IV, and mixed phenotype were significant factors associated with severe exacerbation frequency in univariate analyses. Multivariate analyses showed that lower BMI and CT phenotype were significant factors associated with severe exacerbation frequency. Compared to the CT-normal phenotype, the mixed phenotype was significantly associated with more frequent severe exacerbation (IRR 4.134, 95% CI: 1.135–15.057, P=0.031). CONCLUSION: Patients with mixed phenotype are more symptomatic, have poorer pulmonary function, and are associated with more frequent severe exacerbation.